Microwave-Assisted Synthesis of DUT-52 and Investigation of Its Photoluminescent Properties - Ruth Febriana Kesuma; Aep Patah; Yessi Permana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
A zirconium metal-organic framework (MOF) of DUT-52 (DUT: Dresden University of Technology) was synthesized herein by reacting zirconium tetrachloride (ZrCl4) and 2,6-naphthalenedicarboxylic acid (H2NDC) in DMF under microwave heating at 115 oC for 25 min. This synthetic procedure was more efficient than a solvothermal method, by which a long thermal exposure (24 h) of 100-150 oC was required to produce the same MOF. The MOF has a thermal stability of 560 °C, prior to partial loss of interconnected 2,6-naphthalenedicarboxylate (NDC) linkers at some structure building units (SBU). Crystallinity of this DUT-52 was ca. 77 %, which was the same as one synthesized solvothermally. Diffuse Reflectance UV-Vis spectra revealed an absorption at λex of 287 nm, which was equivalent to a bandgap energy of 4.32 eV. Electron excitations of this DUT-52 at 275 and 300 nm gave emission wavelength of 433 nm (a purple region), indicating a prospective use of DUT-52 as a photoluminescent material.